2023
DOI: 10.1186/s12906-023-03840-0
|View full text |Cite|
|
Sign up to set email alerts
|

A novel therapeutic effect of mannitol-rich extract from the brown seaweed Sargassum ilicifolium using in vitro and in vivo models

Abstract: Background Wound healing is an active, complex, integrated series of cellular, physiological, and biochemical changes initiated by the stimulus of injury in a tissue. The present study was performed to investigate the potential wound healing abilities of Sargassum ilicifolium crude extracts (CE) that were characterized by 1H NMR and FTIR Spectrometric measurements. Materials and methods Seaweed samples were collected from southern coastal sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…This compound belongs to the group of sugar alcohols, the members of which are most widely used as sweeteners for diabetic food products and medication (osmotic diuretic) [ 42 ]. Premarathna et al [ 43 ] reported that the aqueous extract of brown seaweed Sargassum ilicifolium , which also contains D-mannitol, has the potential property of healing skin wounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound belongs to the group of sugar alcohols, the members of which are most widely used as sweeteners for diabetic food products and medication (osmotic diuretic) [ 42 ]. Premarathna et al [ 43 ] reported that the aqueous extract of brown seaweed Sargassum ilicifolium , which also contains D-mannitol, has the potential property of healing skin wounds.…”
Section: Resultsmentioning
confidence: 99%
“…Polar lipids. Among the polar lipids, glycolipids (33, 37, and 44), phospholipid (42), and phosphatidylglycerol (43) were identified in the extract. Two different monoacylglycerols in conjugation with a sulfoquinovosyl part (33 and 37), which differ from each other in terms of the number of carbon atoms and double bonds in the fatty acid side chains, were detected at t R = 16.27 min and 15.90 min with [M − H] − ions at m/z 555.32 and 579.25, respectively.…”
Section: Identification Of Extracts' Chemical Constituents Via the Ch...mentioning
confidence: 99%
“…For marine NPs like fresh seaweeds, initial cleaning with tap water is followed by washing seawater to remove sand particles, epiphytes, and other impurities. Subsequently, the cleaned seaweeds were rinsed with distilled water before preparing extracts [ 85 ]. For metabolomic studies, the extraction procedure is different.…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%
“…For drying, either cryogenic, oven, open-air or freeze drying is used based on the experimental aims and raw materials. NP materials like ESP/parasites need freeze drying, while terrestrial and aquatic plants prefer cryogenic, oven, or air drying [ 85 , 87 ]. However, to extract oil from the plant materials, air drying by maintaining a moderate temperature with proper ventilation is essential to preserve the extracted oil’s flavour, aroma, and therapeutic properties [ 87 ].…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that the first author's affiliation 1 will be "School of Natural Sciences and Health, Tallinn University, Narva mnt 29, 10120 Tallinn, Estonia. Affiliations to authors have been updated and are presented correctly in this correction article.…”
mentioning
confidence: 99%